A rhapsody of love and spirituality - Fekete, David J. (Algora Pub., 2003)
Explores the various facets of love: Platonic eros, Christian mysticism, friendship, religious ritual, and love as people experience it, turning up startling ironies and paradoxes and, along the way, some traditions we may find worth reclaiming.